Pengaruh Ekonomi dan Non-Ekonomi terhadap Emisi Karbon di Negara ASEAN: Analisis Environmental Kuznets Curve - Farah, Najma Taralia; Muhammad Rudi Nugroho (Nuansa Akademik: Jurnal Pembangunan Masyarakat, 2024)
The study aims to determine the effect of carbon emissions on several countries to minimize their impact through Environmental Kuznets Curve (EKC) Analysis. This study uses combined panel data analysis from a cross-section of 6 ASEAN countries with a time series from 2015 to 2023. The results of the model specification test show that the System Generalized Method of Moments approach is the best model to use. It was found that the Population, Government Quality, Economic Growth, Trade Openness and FDI (Foreign Direct Investment) variables have an effect on carbon emissions. The Population, Economic Growth, and Trade Openness variables have a positive and significant effect on carbon emissions. While the Government Quality variable has a negative and significant effect on carbon emissions. However, in the long term the government quality variable has a negative and insignificant effect on carbon emissions and the FDI variable has a significant positive effect on carbon emissions in ASEAN-6 countries from 2015 to 2023.